Pembelajaran IPS Kelas 6 SDN Prekbun Berbasis Proyek untuk Meningkatkan Berpikir Kritis dan Sikap Kewargaan Siswa - Alfinas Syrifah; Annisa Naziatul Azizah; Dinda Aprilia (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2026)
Social Studies (IPS) learning in elementary schools plays an essential role in developing students’ critical thinking skills and civic attitudes as part of 21st-century competencies. However, in practice, IPS learning is still commonly teacher-centered and lacks contextual learning experiences, resulting in low student engagement and limited development of higher-order thinking skills. This study aims to analyze the implementation of Project-Based Learning (PjBL) in IPS learning to enhance critical thinking skills and civic attitudes of grade VI students at SDN Prekbun. The research employed a qualitative approach with a case study design. Data were collected through classroom observations, semi-structured interviews with teachers, students, school principals, and parents, as well as documentation of learning activities. Data analysis was conducted using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing and verification. The findings indicate that the implementation of PjBL effectively enhances students’ active participation, critical thinking skills in analyzing social issues, and civic attitudes such as responsibility, cooperation, and social awareness. Learning becomes more meaningful as students are directly involved in contextual, collaborative, and problem-based project activities. Despite these positive outcomes, several challenges were identified, including limited learning facilities, time management constraints, and variations in students’ confidence levels. This study implies that PjBL is an effective instructional model for strengthening character education and developing 21st-century skills in elementary social studies learning